2021
DOI: 10.1016/j.clml.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Invasive Fungal Infections in Patients With AML Treated With a Hypomethylating Agent

Abstract: The aim of our study was to selectively analyze newly diagnosed patients with acute myeloid leukemia treated with a hypomethylating agent and establish their risk for developing invasive fungal infections (IFIs). We stratified patients into concern for IFI versus no concern, and observed that patients of the male gender and those with underlying chronic obstructive pulmonary disease are at higher risk for concern for IFI, which may prompt clinicians to consider anti-mold prophylaxis in this setting. Background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
2
1
Order By: Relevance
“…Our incidence rate was very similar to the 5.1% incidence rate of probable or confirmed IFI from a recent study that also looked at the use of VEN with either AZA or decitabine in patients with AML [ 9 ]. These consistent rates suggest a lower likelihood of IFI incidence than previously reported rates for newly diagnosed AML cohorts that were similarly treated, where the incidence of proven and possible IFIs was 16% for patients treated with hypomethylating agent–based induction therapy [ 12 ]. In other studies, cohorts that received induction, reinduction, or consolidation chemotherapy plus antifungal prophylaxis reported incidences of proven and probable IFI of 5.9% with antimold prophylaxis and 8.7% without antimold prophylaxis [ 13 ].…”
Section: Discussionsupporting
confidence: 73%
“…Our incidence rate was very similar to the 5.1% incidence rate of probable or confirmed IFI from a recent study that also looked at the use of VEN with either AZA or decitabine in patients with AML [ 9 ]. These consistent rates suggest a lower likelihood of IFI incidence than previously reported rates for newly diagnosed AML cohorts that were similarly treated, where the incidence of proven and possible IFIs was 16% for patients treated with hypomethylating agent–based induction therapy [ 12 ]. In other studies, cohorts that received induction, reinduction, or consolidation chemotherapy plus antifungal prophylaxis reported incidences of proven and probable IFI of 5.9% with antimold prophylaxis and 8.7% without antimold prophylaxis [ 13 ].…”
Section: Discussionsupporting
confidence: 73%
“…As VEN-based therapies are incorporated increasingly commonly into the treatment of MDS, this finding may help to guide treatment selection and infection prevention for previously treated patients. [21][22][23][24] Our analysis demonstrated a relatively higher use of azoles, lower use of echinocandins, and greater proportion of patients without antifungal prophylaxis compared to the study by Aldoss et al 6 These findings illustrate the differences in institutional practices and highlight the need for an evidence-based consensus recommendation for antifungal prophylaxis. Despite these practice differences, neither our study nor that of Aldoss et al 6 identified a significant association between use of antifungal prophylaxis and incidence of IFI.…”
Section: Discussionsupporting
confidence: 50%
“…This result parallels the low average incidence (3%) of probable/confirmed IFI identified in multiple retrospective studies that investigated the use of HMA monotherapy in patients with AML or MDS. As VEN‐based therapies are incorporated increasingly commonly into the treatment of MDS, this finding may help to guide treatment selection and infection prevention for previously treated patients 21–24 …”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the proportion of patients who developed b-IFDs during induction chemotherapy was 1.3% (2/150), one of the lowest among similar studies, even considering those that tested isavuconazole [ 50 , 51 , 52 ], thus, supporting the efficacy of posaconazole AFP in this context. Moving to consolidation chemotherapy, the proportion of our patients experiencing b-IFDs was 1.1% (1/90), lower than in studies conducted before extensive AFP use [ 26 , 60 , 61 , 62 , 63 ] and lower than in the recent study by Del Principe [ 64 ], where AFP was not provided for 44% of patients and the b-IFD incidence among those receiving MAP was 1.5%. Notably, two out of six probable IA in our cohort occurred in patients treated with VEN–HMAs, with 10.5% of patients receiving VEN–HMAs and experiencing b-IFD (2/19), which is similar to the proportion reported in one study [ 57 ] but higher than in other cohorts [ 46 , 75 , 76 , 79 ].…”
Section: Single-center Experience With Posaconazole Prophylaxis In Pa...contrasting
confidence: 68%
“…Finally, AFP with echinocandin resulted in a high rate of b-IFDs in some studies [ 55 , 56 ], but not in others [ 57 , 58 , 59 ]. In addition, studies evaluating AFP effectiveness were historically focused on induction chemotherapy, with few ones exploring the role of AFP, especially MAP, in consolidation chemotherapy, a setting at lower risk of IFDs [ 26 , 60 , 61 , 62 , 63 , 64 ]. Furthermore, IFDs still constitute a major cause of expenditure in HM management [ 65 ]; therefore the prevention of IFDs represents nowadays a major priority.…”
Section: Invasive Fungal Diseases In Patients Undergoing Remission In...mentioning
confidence: 99%